2019
DOI: 10.6002/ect.2017.0086
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of 10 Patients with Cirrhosis Undergoing Emergent Repair of Ruptured Umbilical Hernias: Natural History and Predictors of Outcomes

Abstract: Objectives: Ascites represents an important event in the natural history of cirrhosis, portending increased 1-year mortality. Umbilical herniation with rupture is an uncommon complication of large-volume ascites that is associated with significant morbidity and mortality. The aim of this study was to describe predictors of outcomes in patients undergoing emergent repair for spontaneous umbilical hernia rupture. Materials and Methods:We report a case series of 10 patients with decompensated cirrhosis (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Finally, it is essential to treat these patients in a tertiary center with specialized surgical and intensive care units due to the increased risk of infection, bleeding, and postoperative decompensation of cirrhosis[ 36 ]. Smaller hospitals cannot provide appropriate care because of their lack of experience[ 7 , 37 ]. In such cases, several alternative methods are described, including the successful placement of a pig-tail drain with no recurrence of ascitic fluid leakage and the injection of fibrin glue into the defect to stem drainage[ 38 - 40 ].…”
Section: Which Is the Best Treatment Approach–conservative Treatment Or Urgent Surgery?mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is essential to treat these patients in a tertiary center with specialized surgical and intensive care units due to the increased risk of infection, bleeding, and postoperative decompensation of cirrhosis[ 36 ]. Smaller hospitals cannot provide appropriate care because of their lack of experience[ 7 , 37 ]. In such cases, several alternative methods are described, including the successful placement of a pig-tail drain with no recurrence of ascitic fluid leakage and the injection of fibrin glue into the defect to stem drainage[ 38 - 40 ].…”
Section: Which Is the Best Treatment Approach–conservative Treatment Or Urgent Surgery?mentioning
confidence: 99%
“…This is also known as Flood syndrome, and it was first described by Frank B. Flood in 1961[ 5 , 7 , 8 ]. This is a life-threatening complication with a significant morbidity and mortality rate of 30%.…”
Section: Introductionmentioning
confidence: 99%
“…2,6,9,10 Preoperative medical management should be tailored in conformity to the actual physical state and urgent needs of patients, 22 especially for those with severe encephalopathy or hemodynamic instability; the unstable condition needs to be corrected preoperatively. 6 Malespin et al's 23 recent retrospective study, with small sample sizes of 10 decompensated cirrhotic patients, has demonstrated relatively adverse outcomes after open herniorrhaphy in an emergency setting: 10% mortality and 20% need for urgent liver transplantation.…”
Section: Elective Versus Emergency Surgerymentioning
confidence: 99%
“…In all, 24 of 33 studies [3][4][5][6][7][8][9][10]16,[18][19][20][21][22][23][27][28][29][30][31][32][33][34][35] included cirrhotic patients receiving elective or emergency surgery. Early elective repair of uncomplicated umbilical hernias is recommended in cirrhotic patients with tolerable hepatic functional reserve and good general condition, [3][4][5][6][7]16,[19][20][21] whereas emergency repair is unequivocally indicated by lifethreatening complications, which include rupture, incarceration (not suitable for external reduction), strangulation, and ascites leakage.…”
Section: Elective Versus Emergency Surgerymentioning
confidence: 99%
“…Approximately 20% of patients with ascites eventually develop umbilical hernias as a result of raised intra-abdominal pressure, weakening of anterior abdominal wall muscles from poor nutrition [1,2], and supraumbilical fascial defect due to possible recanalization of the umbilical vein secondary to portal hypertension [3].…”
Section: Introductionmentioning
confidence: 99%